Mucosal grafts and flaps in Draf IIb and Draf III: a systematic review and meta-analysis : systematic review with or without meta-analysis - Lein, Alexander; Liu, David T.; Knerer, Birgit; Mueller, Christian A.; Rotter, Nicole; Vyskocil, Erich; Jaiswal, Archana; Brkic, Faris F.; Bhalla, Rajiv (Otolaryngology - head and neck surgery, 2025)
Abstract Objective To evaluate the impact of mucosal grafts and flaps on neo-ostium patency and clinical outcomes in patients undergoing Draf IIb or III frontal sinus drill-out procedures. Data Sources A systematic search was conducted across PubMed, Medline, Cochrane Library, Scopus, and Web of Science databases in accordance with Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Review Methods Following PRISMA guidelines, consecutive studies were included, and a meta-analysis was performed. Study characteristics, patient demographics, surgical outcomes, and neo-ostium patency rates were extracted. Pooled relative risks (RRs) and mean differences (MDs) were estimated using random-effects models. Publication bias was evaluated via funnel plots and Egger's test. Results Nine studies with 375 patients undergoing mucosal reconstruction were included, following 116 (30.9%) Draf IIb and 259 (69.1%) Draf III procedures. Four comparative studies were eligible for meta-analysis. Draf III was performed in 97.2% of cases (n?=?318), with 165 (51.9%) patients in the flap group and 153 (48.1%) in the no-flap group. Mean follow-up was 41.3?±?9.5 months. Mucosal flaps/grafts significantly improved neo-ostium patency (RR 1.087, 95% CI: 1.018-1.159, P?=?.011) and reduced loss of neo-ostium area (MD 19.52%, 95% CI: 9.97-29.06, P?